Clinical Implications of Vasoactive Intestinal Peptide and 5-Hydroxytryptamine in Diabetic Neurogenic Bladder and Their Relationship with Post-Void Residual Urine Volume - Shi, Long; Zhang, Shaoqi; Cai, Longjun; Zhang, Jianjun; Liu, Gao; Wang, Xiangyu; Ji, Furong; Sun, Yongming; Wei, Zhongqing (Journal of Medical Biochemistry, 2025)
Objective: To elucidate the clinical significance of vasoactive intestinal peptide (VIP) and 5-hydroxytryptamine (5-HT) in diabetic neurogenic bladder (DNB). A key objective is to determine the diagnostic, stratifying, and prognostic value of their simultaneous detection, and to reveal the dynamic associations of these biomarkers with post-void residual urine volume (PVR).Methods: The study population consisted of 30 DNB patients and 30 healthy individuals from the same timeframe (June 2024-April 2025). Laboratory assessments quantified serum VIP concentration by enzyme-linked immunosorbent assay (ELISA) and 5-HT concentration by liquid chromatography-mass spectrometry (LC-MS). PVR quantification relied on urodynamic examination and abdominal ultrasound. Over a 3-month follow-up, serial measurements of VIP and 5-HT were obtained. Statistical analyses, including Pearson correlation, receiver operating characteristic (ROC) curve analysis, and logistic regression modeling, were employed to assess the relationships of these biomarkers with PVR, bladder function classification, and patient prognosis.Results: Significant reductions in VIP and 5-HT were observed in DNB patients relative to controls (P